Effectiveness of seasonal influenza vaccines in children – a systematic review and meta-analysis - Lukšić, Ivana (Croatian Medical Schools, 2013)
AIM: To assess the efficacy and effectiveness of seasonal influenza vaccines in healthy children up to the age of 18 years. METHODS: MedLine, EMBASE, CENTRAL, CINAHL, WHOLIS, LILACS, and Global Health were searched for randomized controlled trials and cohort and case-control studies investigating the efficacy or effectiveness of influenza vaccines in healthy children up to the age of 18 years. The studies were assessed for their quality and data on the outcomes of influenza-like illness, laboratory-confirmed influenza, and hospitalizations were extracted. Seven meta-analyses were performed for different vaccines and different study outcomes. RESULTS: Vaccine efficacy for live vaccines, using random effects model, was as follows: (i) for similar antigen, using per-protocol analysis: 83.4% (78.3%-88.8%); (ii) for similar antigen, using intention to treat analysis: 82.5 (76.7%-88.6%); (iii) for any antigen, using per protocol analysis: 76.4% (68.7%-85.0%); (iv) for any antigen, using intention to treat analysis: 76.7% (68.8%-85.6%). Vaccine efficacy for inactivated vaccines, for similar antigen, using random effects model, was 67.3% (58.2%-77.9%). Vaccine effectiveness against influenza-like illness for live vaccines, using random effects model, was 31.4% (24.8%-39.6%) and using fixed-effect model 44.3% (42.6%-45.9%). Vaccine effectiveness against influenza-like illness for inactivated vaccines, using random effects model, was 32.5% (20.0%-52.9%) and using fixed-effect model 42.6% (38.3%-47.5%). CONCLUSIONS: Influenza vaccines showed high efficacy in children, particularly live vaccines. Effectiveness was lower and the data on hospitalizations were very limited.